Intrinsic Au-decoration on anodic TiO2 nanotubes grown from metastable Ti–Au sputtered alloys—High density co-catalyst decoration enhances the photocatalytic H2 evolution. (March 2019) - Hejazi, Seyedsina; Altomare, Marco; Nguyen, Nhat Truong; Mohajernia, Shiva; Licklederer, Markus; Schmuki, Patrik
Abstract : Graphical abstract: Highlights: We produce metastable Ti–Au alloy layers by Ti and Au cosputtering. The Au concentration can exceed the solubility limit of Au in Ti–Au solid solutions. The Ti–Au layers are used to grow anodic TiO2 nanotubes with intrinsic Au decoration. The Au nanoparticle density is higher than using classic alloys. The result is a 15-times higher photocatalytic H2 evolution rate. Abstract: Recent work demonstrated that intrinsic Au nanoparticle decoration of TiO2 nanotube arrays (NTs) can be achieved by electrochemical anodization of Ti–Au alloy substrates. However, for a Ti–Au cast alloy produced by melt-alloying, the Au concentration cannot exceed the solubility limit of Au in Ti of 0.2 at.% – this sets constraints on the intrinsic Au nanoparticle loading on anodic TiO2 NTs. Here we explore "metastable" Ti–Au metal substrates that are produced by Ti and Au cosputtering and we establish Au concentrations that far exceed the solubility limit in cast Ti–Au alloys. We show the use of these "metastable" Ti–Au sputtered layers for the anodic formation of TiO2 NTs with a much higher density of Au nanoparticle loading than using classic alloys. Under optimized conditions (Au nanoparticle density) photocatalytic H2 production from such Au@TiO2 platforms provides a 15 times higher photocatalytic H2 evolution rate than the best rates achieved with conventional alloys.